Pelizaeus-Merzbacher Disease, Pelizaeus-Merzbacher-Like Disease 1, and Related Hypomyelinating Disorders - Hobson, Grace M.; Garbern, James Y. (Seminars in Neurology, 2012)
The purpose of this article is to present contemporary information on the clinical and molecular diagnosis and the treatment of Pelizaeus-Merzbacher's disease (PMD) and related leukodystrophies. Various types of mutations of the X-linked proteolipid protein 1 gene (PLP1) that include copy number changes, point mutations, and insertions or deletions of a few bases lead to a clinical spectrum from the most severe connatal PMD, to the least severe spastic paraplegia 2 (SPG2). Signs of PMD include nystagmus, hypotonia, tremors, titubation, ataxia, spasticity, athetotic movements and cognitive impairment; the major findings in SPG2 are leg weakness and spasticity. A diffuse pattern of hypomyelination is seen on magnetic resonance imaging (MRI) of PMD/SPG2 patients. A similar constellation of signs and pattern of hypomyelination lead to the autosomal recessive disease called Pelizaeus-Merzbacher-like disease 1 (PMLD1) and the less-severe spastic paraplegia 44 (SPG44), caused by mutations of the gap junction protein, gamma-2 gene (GJC2), formerly known as the gap junction protein, α-12 gene (GJA12). Magnetic resonance spectroscopy (MRS) and brainstem auditory evoked potentials (BAEP) may assist with differential clinical diagnosis of PMD and PMLD1. Supportive therapy for patients with PMD/SPG2 and PMLD1/SPG44 includes medications for seizures and spasticity; physical therapy, exercise, and orthotics for spasticity management; surgery for contractures and scoliosis; gastrostomy for severe dysphagia; proper wheelchair seating, physical therapy, and orthotics to prevent or ameliorate the effects of scoliosis; special education; and assistive communication devices.
Keywords: Pelizaeus-Merzbacher disease; spastic paraplegia 2; Pelizaeus-Merzbacher-like disease; spastic paraplegia 44